IMPLEMENTASI GREEN ECONOMY TERHADAP PEMBANGUNAN EKONOMI BERKELANJUTAN DI INDONESIA - Miranda Aprilia; Riska Aprilia; Isma Sofia Rahma; Reni Indriani (Yayasan Insani Mandiri Santani, 2026)
This study aims to analyze the implementation of a green economy towards sustainable economic development in Indonesia. A green economy is a development approach that emphasizes a balance between economic growth, environmental sustainability, and social welfare. The research method used is a literature review with a qualitative descriptive approach through the collection and analysis of various literature sources from national and international scientific journals. The results of the study indicate that a green economy plays a crucial role in supporting sustainable economic development by increasing resource efficiency, reducing carbon emissions, creating green jobs, and encouraging environmentally friendly technological innovation. Furthermore, a green economy also contributes to strengthening economic resilience and improving the quality of long-term development. However, the implementation of a green economy in Indonesia still faces various obstacles such as limited infrastructure, low public awareness, dependence on the extractive sector, and limited investment in the green sector. Keywords: Green Economy, Sustainable Economic Development, Green Economy, Sustainable Development, Indonesia